A mixed methods approach in analyzing the perspective of Croatia’s economic relations with the U.S., Russia, and China - Megits, Nikolay (Mykola); Wittine, Zoran; Liu, Ran; Schuster, Julian Z. (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This study explores the relationship between Croatia and the U.S., Russia, and China, providing a comparative qualitative analysis of trade and investment flows between these countries. Using a Mixed Methods approach combined with a literature review, evaluation of a range of data sources, analysis of bilateral trade data and foreign direct investment flows, and other economic indicators, the study analyzes the drivers of and implications for economic ties between Croatia and these countries. The study also examines the impact of economic sanctions on Croatia's relationship with Russia. The research finds that the U.S. is Croatia's largest trading partner, while Russia and China are important sources of foreign direct investment. Finally, the study provides recommendations for future research, highlighting the need for a greater focus on trade in services, investment flows, and comparative analysis with other countries in the Balkans region. Overall, the study contributes to understanding the complex economic relationship between Croatia and the U.S., Russia, and China and offers recommendations for greater diversification of Croatia's trade and investment partners and the importance of monitoring the political and economic risks in economic cooperation.